Epigallocatechin-3-gallate (EGCG) for clinical trials: more pitfalls than promises? - Mereles, Derliz; Hunstein, Werner (International journal of molecular sciences, 2011)
Epigallocatechin-3-gallate (EGCG), the main and most significant polyphenol in green tea, has shown numerous health promoting effects acting through different pathways, as antioxidant, anti-inflammatory and anti-atherogenic agent, showing gene expression activity, functioning through growth factor-mediated pathways, the mitogen-activated protein kinase-dependent pathway, the ubiquitin/proteasome degradation pathway, as well as eliciting an amyloid protein remodeling activity. However, epidemiological inferences are sometimes conflicting and in vitro and in vivo studies may seem discrepant. Current knowledge on how to enhance bioavailability could be the answer to some of these issues. Furthermore, dose levels, administration frequency and potential side effects remain to be examined.